The metabolic pH response in Lactococcus lactis: an integrative experimental and modelling approach - Andersen, Ann Zahle; Kummer, Ursula (Computational biology and chemistry, 2009)
Lactococcus lactis is characterised by its ability to convert sugar almost exclusively into lactic acid. This organic acid lowers extracellular pH, thus inhibiting growth of competing bacteria. Although L. lactis is able to survive at low pH, glycolysis is strongly affected at pH values below 5, showing reduced rate of glucose consumption. Therefore, in order to deepen our knowledge on central metabolism of L. lactis in natural or industrial environments, an existing full scale kinetic model of glucose metabolism was extended to simulate the impact of lowering extracellular pH in non-growing cells of L. lactis MG1363. Validation of the model was performed using 13C NMR, 31P NMR, and nicotinamide adenine dinucleotide hydride auto-fluorescence data of living cells metabolizing glucose at different pH values. The changes in the rate of glycolysis as well as in the dynamics of intracellular metabolites (NADH, nucleotide triphosphates and fructose-1,6-bisphosphate) observed during glucose pulse experiments were reproduced by model simulations. The model allowed investigation of key enzymes at sub-optimum extracellular pH, simulating their response to changing conditions in the complex network, as opposed to in vitro enzyme studies. The model predicts that a major cause of the decrease in the glycolytic rate, upon lowering the extracellular pH, is the lower pool of phosphoenolpyruvate available to fuel glucose uptake via the phosphoenolpyruvate-dependent transport system.